(untitled) (Jazykovedný časopis, 2026)
Political communication is one of the socially relevant forms of public communication. Political style is characterized by being strategic and success-oriented (the goal is to influence public opinion or create a certain ideological climate). However, by engaging in the disinformation discourse, persuasion is marked by an increased degree of communicative manipulation. A manipulative communication style is characterized by a specific instrumentalization of language. The analysis of communication style focuses on the development of the topic of so-called “liberal fascism,” which, as a term, is the target of public criticism. The effectiveness of political communication is ensured by the overall stylistic shaping of texts, meaning that attention is primarily focused on the ways of presenting the speech and creating suitable (interpretative) conditions for achieving a certain effect. The aim of this paper was to analyse the methods of manipulation in political communication, which are developed in all of its aspects, i.e. at the level of the content, at the level of self-presentation, at the level of relationship and at the level of appeal.